Benefits of Skill Chaining in Serial Production Lines with Cross-Trained Workers - Hopp, Wallace J.; Tekin, Eylem; Van Oyen, Mark P. (Management Science, 2004)
To gain insight into the potential logistical benefits of worker cross-training and agile workforce policies, we study simple models of serial production systems with flexible servers operating under a constant work-in-process (CONWIP) release policy. Two important and interrelated issues are: (a) how to decide which skill(s) are strategically most desirable for workers to gain, and (b) how to coordinate these workers to respond dynamically to congestion. We address these by considering two cross-training strategies: a straightforward capacity-balancing approach, which we call cherry picking (CP), and an innovative overlapping zone strategy that we call skill chaining. Our comparison shows that skill-chaining strategies have the potential to be robust and efficient methods for implementing workforce agility in serial production lines.